How to master negotiation - Carroll, Eileen; Balassa, Balint; Oppenheimer, Leah (Online access with DDA: Askews (Psychology), 2015)
'How to Master Negotiation' provides individuals with a guide of how to prepare themselves and others for a variety of negotiations - ranging from instantly recognisable transactions, such as deal negotiations, to the more intricate organisational and interpersonal negotiations that often give rise to conflict.